2013
DOI: 10.1159/000355103
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin Trometamol (3,000 mg) in Perioperative Antibiotic Prophylaxis of Healthcare-Associated Infections after Endourological Interventions: A Narrative Review

Abstract: Introduction: Increasing antibiotic resistance also has an impact on perioperative antibiotic prophylaxis (PAP). This narrative review evaluates fosfomycin trometamol (FT) as PAP in endourological interventions. Materials and Methods: Nine clinical studies including 4 randomized comparative studies were analyzed. A total of 1,614 patients received FT as PAP for different endourological procedures and extracorporeal shock wave lithotripsy [ESWL; i.e. cystoscopy (n = 498), urodynamic studies (n = 39), ureteropye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…Recently, Wagenlehner et al [3] reported that fluoroquinolones were used in 98.2 % of patients, but resistance against fluoroquinolones was seen in 60 % of all bacterial strains isolated after the procedure. An alternative strategy to the fluoroquinolone-based prophylaxis is therefore needed [9,27]. Here, we performed a retrospective cohort analysis in patients who underwent TR-PB and demonstrated that FT may be an attractive alternative antimicrobial prophylaxis for TR-PB due to a lower rate of symptomatic UTIs and a lower rate of adverse events as compared with CIP.…”
Section: Main Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Wagenlehner et al [3] reported that fluoroquinolones were used in 98.2 % of patients, but resistance against fluoroquinolones was seen in 60 % of all bacterial strains isolated after the procedure. An alternative strategy to the fluoroquinolone-based prophylaxis is therefore needed [9,27]. Here, we performed a retrospective cohort analysis in patients who underwent TR-PB and demonstrated that FT may be an attractive alternative antimicrobial prophylaxis for TR-PB due to a lower rate of symptomatic UTIs and a lower rate of adverse events as compared with CIP.…”
Section: Main Findingsmentioning
confidence: 98%
“…Thus, infectious complications after TR-PB represent an important challenge for the urologist and for patients. On the other hand, several authors reported that fosfomycin trometamol (FT) could be a valid alternative for antibiotic prophylaxis of TR-PB due to its low profile of resistance, elevated activity against multidrug-resistant (MDR) Gram-negative bacteria and favorable pharmacokinetic properties [8][9][10]. Here, we aimed to compare the clinical outcome of patients who underwent TR-PB and received prophylaxis with either FT or ciprofloxacin (CIP), by means of a retrospective, comparative cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published review regarding the effectiveness of fosfomycin in preventing UTI after endourological interventions or surgical procedures, the authors concluded that one or two doses of fosfomycin trometamol could be an effective alternative. The conclusion was limited by the small number of available patients for every indication (253). In an RCT not included in that review, fosfomycin (3 g by mouth every 48 h for two doses) was compared with ciprofloxacin (500 mg by mouth every 12 h for 5 days) for prevention of prostatitis after transrectal prostate biopsy; 671 patients were enrolled.…”
Section: Prophylaxismentioning
confidence: 99%
“…Herr's study was on the frequency of UTIs in patients with bladder cancer and after BCG treatment [21]. Alsaywid et al and Wagenlehner et al, produced review articles [22,23], while Hori and Kennedy's article is a commentary on one of the included studies [24]. …”
Section: Evidence Synthesismentioning
confidence: 99%